Effects of filtered cathodic vacuum arc deposition (FCVAD) conditions on photovoltaic TiO2 films - C. Aramwit (2018)
Titanium dioxide (TiO2) films for photovoltaic applications were synthesized using filtered cathodic vacuum arc deposition (FCVAD) technique. Various deposition conditions were tested for an optimal film formation. The conditions included the oxygen (O2) pressure which was varied from a base pressure 10-5to 10-4, 10-3, 10-2and 10-1Torr, sample holder bias varied using 0 or -250 V, deposition time varied from 10, 20 to 30 min, and deposition distance varied from 1 to 3 cm. The deposited films were also annealed and compared with unannealed ones. The films under various conditions were characterized using optical microscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), energy-dispersive X-ray spectroscopy (EDS) and Raman spectroscopy techniques. The film transparency increased and thickness decreased to a nanoscale with increasing of the O2pressure. The transparent deposited films contained stoichiometric titanium and oxygen under the medium O2pressure. The as-deposited films were TiO2containing some rutile but no anatase which needed annealing to form. © 2014 Elsevier B.V.